A STUDY ON THE EFFECT OF NOISE AND VIBRATION ON OPERATORS’ READABILITY TASK PERFORMANCE IN A MOBILE DRIVING ENVIRONMENT - Iqbal Ahmed Khan; Z. Mallick; Zahid A. Khan (Universitas Gadjah Mada, 2008)
This paper presents a study in which the effect of noise and vibration on the task performance in a mobile driving environment is experimentally investigated. A readability kind of task, where a reading material was presented to the operators on a laptop screen was considered and the operators performed the task in a sitting posture without their back supported with the backrest of the seat. The task performance was measured in terms of mean number of characters read per minute by the operators, which served as data for statistical analysis. Results of the study showed that noise and vibration were statistically significant. The interaction between gender and vibration was also found to be significant. The presence of noise and vibration in a mobile environment decreased the operators’ task performance. The results of the simple main effect analysis indicated that the gender was statistically significant for the last two levels of vibration. However the equivalent acceleration of vibration was found statistically significant for males and females. The findings are in line with previous researches that showed negative significant effect of noise and vibration on operators’ task performance.